How are Youth Faring in the Labor Market? Evidence from Around the World - Fares, Jean; Montenegro, Claudio E.; Orazem, Peter F. (World Bank, Washington, DC, 2012)
This paper uses a new standardized micro database for a large set of developing countries to (1) describe the patterns of labor market outcomes for youth, and (2) explain the contributions of supply and demand factors to youth outcomes. The paper shows that youth face various difficulties in transitioning to work. This is reflected in their relatively higher unemployment rate, higher incidence of low paying or unpaid work, and a large share of youth who are neither working nor in school. This is especially true for young girls who are found outside the labor market, some engaged in home production. Finally, the paper also finds that cross-country estimates show that changes in the youth relative cohort size is unlikely to have a large effect on how youth are faring in the labor market.